Risk of Pancreatic Cancer in the Long-Term Prospective Follow-Up of Familial Pancreatic Cancer Kindreds. (27th August 2022) - Porter, Nancy; Laheru, Daniel; Lau, Bryan; He, Jin; Zheng, Lei; Narang, Amol; Roberts, Nicholas J; Canto, Marcia I; Lennon, Anne Marie; Goggins, Michael G; Hruban, Ralph H; Klein, Alison P
Abstract: Background: A family history of pancreatic cancer is associated with increased pancreatic cancer risk. However, risk estimates for individuals in kindreds with an aggregation of pancreatic cancer (>1 relative) are imprecise because of small samples sizes or potentially impacted by biases inherent in retrospective data. Objective: The objective of this study is to determine the age-specific pancreatic cancer risk as a function of family history using prospective data. Methods: We compared pancreatic cancer incidence (n = 167) in 21 141 individuals from 4433 families enrolled in the National Familial Pancreatic Cancer Registry with that expected based on Surveillance Epidemiology and End Results data and estimated the cumulative probability of pancreatic cancer using competing risk regression. Results: Familial pancreatic kindred members (kindreds with pancreatic cancer in 2 first-degree relatives [FDRs] or a pathogenic variant) had a standardized incidence ratio of 4.86 (95% confidence interval [CI] = 4.01 to 5.90), and sporadic kindred members (kindreds not meeting familial criteria) had a standardized incidence ratio of 2.55 (95% CI = 1.95 to 3.34). Risk in familial pancreatic cancer kindreds increased with an increasing number of FDRs with pancreatic cancer, with a standardized incidence ratio of 3.46 (95% CI = 2.52 to 4.76), 5.44 (95% CI = 4.07 to 7.26), and 10.78 (95% CI = 6.87 to 16.89) for 1, 2, and 3 or more FDRs with pancreatic cancer, respectively. Risk was also higher among individuals with a family history of young-onset (aged younger than 50 years) pancreatic cancer. Conclusion: Pancreatic cancer risk is strongly dependent on family history, including both the degree of relationship(s) and age of onset of pancreatic cancer in relatives. These risk estimates will help inform the design of early detection studies and the risk and benefit analysis of screening trials.